Delirium: nursing interventions directed to the hospitalized adult patient – a bibliographic review - Bento, Marta Sofia Pão Mole (2021)
Delirium is a neuropsychiatric syndrome, characterized by an acute attention and cognition deficit disorder, of multifactorial etiology. It has a high prevalence in the elderly population and it’s an indicator of a poor prognosis. It leads to a negative impact, provoking deterioration in the person’s quality of life. Objectives: This study aimed to identify the nursing interventions directed to the hospitalized adult / elderly, for the control of delirium. Methodology: Using a PICO question as a reference, a review of articles published between 2012 and 2017 was carried out. That identified, which nursing interventions aimed at the adult / elderly person hospitalized with delirium. Results: In this bibliographic review 5 studies were selected, in common, they present tendentially, non-pharmacological dynamic strategies of preventive character towards the delirium. This evidences the role of nursing in carrying out preventive actions (preferentially directed to risk factors, which may trigger this neurological alteration), such as the maintenance of the sensorial balance, assessing the local environment, monitoring pain, sleep and the stimulation of the early mobility. Conclusion: The interventions for delirium should include the identification of predisposing and precipitating factors with adequate actions, for its resolution. Research is imperative, to recognize and validate witch interventions may control delirium (prevent/ treat) and thus reduce its consequences.